EFEKTIVITAS KOMUNIKASI WEBSITE kitabisa.com SEBAGAI MEDIA MENGGALANG DANA DAN BERDONASI ONLINE (CROWDFUNDING) - Ulfa, Maria; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Kitabisa.com is a foundation engaged in the social field. Kitabisa.com is a platform to raise funds and donate online (crowdfunding). Kitabisa.com has a variety of features that are more complete than on the website crowdfunding its competitors. Crowdfunding is crowd funding from the community or can be called a joint venture against a business or project. As the number one crowdfunding website in Indonesia, researchers are interested in analyzing the level of communication effectiveness of the website kitabisa.com and which indicators of communication effectiveness are most effective. This study aims to determine how large the scale of the effectiveness of communication website kitabisa.com as a medium to raise funds and contribute online (crowdfunding).This study uses quantitative research methods with purposive sampling techniques. Data collection through the distribution of questionnaires through the internet to 100 respondents. Data analysis techniques in this study used descriptive statistical techniques. Data testing was carried out with SPSS for Windows version 21.The results of this study stated that the website bukisa.com was effective as a media to raise funds and donate online (crowdfunding). These results were obtained from data processing communication effectiveness variables according to Andre Hardjana consisting of six indicators. Each indicator gets different results. Indicators receiver(receiver)medapat get the value 3.07, the message(content)of 3.23, the media messages(media)of 3.26, the message format(format)of 3.25, the source of the message(source)of 3.22, timekeeping(timing) 3.19. The highest get the value is obtained by the media message indicator and the lowest get the  value is obtained by the recipient indicator. The results obtained based on the average formula of all indicators are 3.2 which are included in the effective scale range.   Key word : Communication Effectivity, Crowdfunding, kitabisa.com